Modelling of rotary kiln incinerator for the disposal of hazardous waste / Anas Mohd Rashid, Mohamed Syazwan Osman and Mohd Rashid Mohd Yusof - Mohd Rashid, Anas; Osman, Mohamed Syazwan; Mohd Yusof, Mohd Rashid (2020)
The generation of hazardous wastes is currently increasing in Malaysia. These wastes originated from industrial and medical related activities, which pose health risk to human and the environment. There are various methods of treatment available for the disposal of these wastes such as thermal and non-thermal technique. However, the thermal treatment through incineration is found to be the best available option for the disposal of these hazardous wastes because it is fast and complete reaction with tremendous volume reduction. Typically and commercially, rotary kiln type incinerator is commonly used for this purpose as it can handle any combination of wastes may it be in the form of solid, liquid, or sludge. Thus, this study presents the modeling of rotary kiln incinerator based on a typical hazardous waste composition taken into consideration of three main inputs, which are waste inlet, excess air inlet, and fuel inlet with flue gas outlet as the main output by using the Microsoft Excel spreadsheet. Reliability of model is determined by comparing the percentage error of flue gas composition between two (2) different compositions of typical hazardous waste. For both values, it is found that the percentage errors are 0.31% and 1.20% respectively. Model was able to predict a low percentage error of 5% and below. Addition data can be tested for further determination of the model’s reliability